The arrangements of the microvasculature and surrounding glial cells are linked to blood–brain barrier formation in the cerebral cortex - Shigemoto-Mogami, Yukari; Nakayama-Kitamura, Kimiko; Sato, Kaoru (Frontiers in Neuroanatomy, 2024)
The blood–brain barrier (BBB) blocks harmful substances from entering the brain and dictates the central nervous system (CNS)-specific pharmacokinetics. Recent studies have shown that perivascular astrocytes and microglia also control BBB functions, however, information about the formation of BBB glial architecture remains scarce. We investigated the time course of the formation of BBB glial architecture in the rat brain cerebral cortex using Evans blue (EB) and tissue fixable biotin (Sulfo-NHS Biotin). The extent of the leakage into the brain parenchyma showed that the BBB was not formed at postnatal Day 4 (P4). The BBB gradually strengthened and reached a plateau at P15. We then investigated the changes in the configurations of blood vessels, astrocytes, and microglia with age by 3D image reconstruction of the immunohistochemical data. The endfeet of astrocytes covered the blood vessels, and the coverage rate rapidly increased after birth and reached a plateau at P15. Interestingly, microglia were also in contact with the capillaries, and the coverage rate was highest at P15 and stabilized at P30. It was also clarified that the microglial morphology changed from the amoeboid type to the ramified type, while the areas of the respective contact sites became smaller during P4 and P15. These results suggest that the perivascular glial architecture formation of the rat BBB occurs from P4 to P15 because the paracellular transport and the arrangements of perivascular glial cells at P15 are totally the same as those of P30. In addition, the contact style of perivascular microglia dramatically changed during P4-P15.